IMPLEMENTATION OF THE DASA DHARMA VALUES OF SCOUTING IN DEVELOPING LEADERSHIP CHARACTER IN STUDENTS - Lisnawati; Eldi Mulyana; Jaenal Mutaqin, Andre (Institut Pendidikan Indonesia, 2025)
The current generation faces various challenges that affect the formation of character and leadership in students. One of the main challenges is the influence of technology and social media. The Dasa Dharma Pramuka, which consists of ten main values, is a guideline for Scout members to form strong character and leadership. This study used a descriptive qualitative approach on students at MA Persis Tarogong, Garut. Data were collected through interviews, observations, and document analysis. The results of the study showed that the implementation of the Dasa Dharma Pramuka values ​​significantly contributed to the formation of student leadership character. Students who were active in Scout activities showed an increase in discipline, responsibility, courage, and the ability to work together. Values ​​such as love of nature, compassion for fellow human beings, and willingness to help, became a strong moral foundation in their daily lives. In addition, various Scout activities, such as camping, social services, and community service projects, provided practical experiences that strengthened the understanding and application of the Dasa Dharma values. The conclusion of this study is that 1) The Dasa Dharma Pramuka is effective in developing leadership character in students. 2) A supportive school environment, the active role of Scout leaders, and the involvement of the principal are essential for the successful implementation of these values. 3) This study recommends that schools better integrate Scouting activities into the curriculum and strengthen collaboration with families and communities to create an environment conducive to the development of character and leadership in students.